Immunological response in horses following West Nile virus vaccination with inactivated or recombinant vaccine - Monaco, Federica; Purpari, Giuseppa; Di Gennaro, Annapia; Mira, Francesco; Di Marco, Patrizia; Guercio, Annalisa; Savini, Giovanni (Veterinaria Italiana, 2019)
To evaluate the immunological response following vaccination, 40 WNV serologically negative horses were selected and divided in two groups of 20 animals. One group was vaccinated (booster after 28 days) with a whole inactivated viral strain and the second group with a live recombinant canarypox virus expressing the genes coding for the WNV preM/E viral proteins. IgM, IgG and neutralizing antibodies were monitored by class specific ELISAs and serum neutralization assay for 360 days. In both groups, IgM antibodies were first detected 7 days post vaccination (dpv). However, in the group vaccinated with inactivated vaccine, IgM antibodies were detected until day 42 pv, whereas in the group vaccinated with the recombinant vaccine, they were detected up to day 52 pv. A similar (P > 0.05) proportion of horses showed IgM antibodies after vaccination with either recombinant [30%; 95% confidence interval (CI): 14.59%-52.18%] or inactivated (32%; 95% CI: 15.39-54.28%) vaccine. Both vaccines induced in vaccinated horses a detectable IgG antibody response starting from day 7 pv and lasting till the end of the trial. Analogously, both products elicited WNV specific neutralizing antibodies. The response induced by the live canarypox virus-vectored vaccine was higher (mean titres 1:298 vs 1:18.9) and lasted longer than did that induced by the killed-virus vaccines. In fact, one year after the vaccination, neutralizing antibodies were still detectable in the horses which received the canarypox virus-based vaccine but not in the group vaccinated with the killed product. The use of vaccines is a valuable tool to prevent WNV disease in horses and the availability of different products facilitates the control of the disease in endemic areas.